2015
DOI: 10.1016/j.jacc.2015.08.862
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis, Connexin-43, and Conduction Abnormalities in the Brugada Syndrome

Abstract: BackgroundThe right ventricular outflow tract (RVOT) is acknowledged to be responsible for arrhythmogenesis in Brugada syndrome (BrS), but the pathophysiology remains controversial.ObjectivesThis study assessed the substrate underlying BrS at post-mortem and in vivo, and the role for open thoracotomy ablation.MethodsSix whole hearts from male post-mortem cases of unexplained sudden death (mean age 23.2 years) with negative specialist cardiac autopsy and familial BrS were used and matched to 6 homograft control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
290
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(335 citation statements)
references
References 34 publications
(50 reference statements)
14
290
0
8
Order By: Relevance
“…Ohkubo et al also reported prolonged QRS duration of more than 120 ms, as measured on a standard ECG, that is associated with life‐threatening ventricular arrhythmia in BrS 9. These findings occur because of abnormal slow and fragmented epicardial electrograms from reduction in gap junction expression at right ventricular outflow tract evidenced by autopsies 11. These abnormal electrograms caused by cardiac conduction delay may lead to generate reentry of ventricular arrhythmia, as shown in this study, by appropriate ICD therapy in BrS patients (Table 1).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Ohkubo et al also reported prolonged QRS duration of more than 120 ms, as measured on a standard ECG, that is associated with life‐threatening ventricular arrhythmia in BrS 9. These findings occur because of abnormal slow and fragmented epicardial electrograms from reduction in gap junction expression at right ventricular outflow tract evidenced by autopsies 11. These abnormal electrograms caused by cardiac conduction delay may lead to generate reentry of ventricular arrhythmia, as shown in this study, by appropriate ICD therapy in BrS patients (Table 1).…”
Section: Discussionmentioning
confidence: 95%
“…These SCN5A polymorphisms could decrease expression of sodium‐channel proteins and alter gating properties resulting in prolongation of the QRS duration and slow conduction in the heart 7, 9. The SCN5A mutations may be associated with early and frequent VF recurrence or SCA in BrS patients, which may be related to fibrosis in the right ventricular outflow tract epicardial surface 10, 11. Most studies on SCN5A mutations included both asymptomatic and symptomatic BrS patients 8, 9, 10, 11.…”
Section: Introductionmentioning
confidence: 99%
“…35 Consistent with this, tissue samples from the right ventricular outflow tract of patients with Brugada syndrome carrying SCN5A mutations, exhibited epicardial and myocardial fibrosis. 36 In our hiPSC model, we found no significant difference in Ca 2+ transient measurements between the D1275N and Control cells. Further investigations are needed to elucidate the causing mechanism of SCN5A-related DCM.…”
Section: Discussionmentioning
confidence: 51%
“…23 Postmortem analyses of unexplained sudden death victims in different series were all concordant in describing peculiar tissue abnormalities at the RVOT, 24 characterized by reduced connexin-43 expression, interstitial fibrosis, 25 and activation slowing that conditions an absent transmural repolarization gradient, and abnormal conduction restitution. 26 To date, both theories are believed to be involved in the etiopathogenesis of BrS as demonstrated by an elegant study of ECG imaging on 25 BrS and 6 RBBB patients; unlike BrS, RBBB showed delayed activation in the entire RV, without ST-segment elevation, fractionation, or repolarization abnormalities. 27 penetrance 8,12 (i.e., the abnormal gene is inherited by 50% of the offspring, and both males and females equally inherit the defective gene, but not all will develop the disease).…”
Section: Historymentioning
confidence: 99%